Factors that Influence Students' Choice of the Most Preferred Instrumental Ensemble in Selected Schools in Klang Valley - Lee, Yoke Fun (2004)
This study sought to determine the influence of the teacher, the social environmental, the nature of the instrument and the repertoire of the ensemble on the Fom Three students' choice of the most preferred instrumental ensemble. The instrumental ensemble in this study comprises of the kompn, cakiempong, gamelm, keyboard and recorder ensembles. It also aimed to determine which instrumental ensemble in schools is most preferred by the students. It also sought to identifj, the reasons as to why certain factors had significant influence on the students' choice of the most preferred instrumental ensemble. Questionnaires were distributed to 161 Form Three students who served as subjects. The distribution of the questionnaire was to obtain feedback about their choices for the tnost preferred instrutnental ensemble and the influence of the selected factors on their choices. This study utilized statistical analysis such as the descriptive statistics and binary logistic regression. This study was carried out for over an established period of twelve sessions of music lessons in Sekolah Menengah Kebangaan Cheras, Cheras (n=44), Sekolah Menengah Kebangsaan Bandar Bani Sentul, Sentul (n=58), Sekolah Menengah Kebangsaan Seksyen 19, Shah Alarn (n=43) and Sekolah Menengah Kebangsaan Dato' Hamzah, Pelabuhan Klang (n= 16). The research findings indicate that the most preferred instrumental ensemble is the gumelan ensemble followed by the keyboard ensemble, kimpng ensemble, cakfempong ensemble and lastly the recorder ensemble. The findings also revealed that the teacher factor has siguificant influence on the students' choice of the gamelan, kompang and the caklempong ensemble as the most preferred instrumental ensemble. Whereby, the nature of the instrument factor has significant influence on the students' choice of the gamelan, keyboard and the konlpang ensemble as the most preferred instnunental ensemble. The research findings also indicate that the repertoire ofthe ensemble fBctor has significant influence on the students' choice of the ga~treiat~au d the konlpang ensemble as the most preferred instrumental ensemble. It is also discovered that all the factors do not have sigiificant influence on the students' choice of the recorder ensenlble as the most preferred instrumental ensemble. It is hoped that this study will provide information to fill in the gap of knowledge about the factors, which influence the students' choice of the most preferred instrumental ensemble. These influential factors are important because these factors will eventually be the intrinsic motivating factors that can motivate the students thus sustaining their interest in the instrumental ensemble learning. The sustenance of the interest can fhther lead them to geater achievement in instrumental ensemble learning. Lastly, it is hoped that the findings of this study will benefit the music teachers as well as for the students and concerned parties who are directly or indirectly involved in the music education.